2022
DOI: 10.13057/biodiv/d230231
|View full text |Cite
|
Sign up to set email alerts
|

Chlorogenic acid and caffeine content of fermented robusta bean

Abstract: Abstract. Purwoko T, Suranto, Setyaningsih R, Marliyana SD. 2021. Chlorogenic acid and caffeine content of fermented robusta bean. Biodiversitas 23: 902-906. Robusta beans contain caffeine and chlorogenic acid higher than arabica beans, however, it has a lower economic value than arabica beans. Therefore, microorganisms in the robusta bean for the fermentation process are expected to reduce caffeine and chlorogenic acid contents. The objective of this research was to investigate the ability of fungus Rhizopus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 22 publications
(32 reference statements)
0
13
0
Order By: Relevance
“…4 a). A previous study showed that both yeasts and LAB were able to decrease caffeine content by absorbing or degrading caffeine due to its structural similarity to the purine molecule ( Purwoko et al, 2022 ). In addition, caffeine in SL samples could have also been degraded to theobromine and theophylline by yeast through N- demethylation ( Hakil et al, 1998 ).…”
Section: Resultsmentioning
confidence: 99%
“…4 a). A previous study showed that both yeasts and LAB were able to decrease caffeine content by absorbing or degrading caffeine due to its structural similarity to the purine molecule ( Purwoko et al, 2022 ). In addition, caffeine in SL samples could have also been degraded to theobromine and theophylline by yeast through N- demethylation ( Hakil et al, 1998 ).…”
Section: Resultsmentioning
confidence: 99%
“…Coffea canephora , popularly known for its variety Coffea robusta (Robusta coffee), is native to Central Africa, and its cultivation is popular in Asian countries and in Brazil [ 30 , 31 ]. In contrast to Arabica coffee, Robusta contains higher levels of caffeine, giving it a stronger bitter taste.…”
Section: Coffeementioning
confidence: 99%
“…It presents characteristics of allogamous reproduction and gametophytic self-incompatibility, making cross-fertilization the only form of sexual reproduction of the species [ 28 , 35 ]. Coffee trees of Coffea robusta are multi-stem, with a phenological cycle (9–11 months) longer than Coffea arabica [ 31 ].…”
Section: Coffeementioning
confidence: 99%
“…Previous research showed that L. casei, L. mesenteroides, R. oryzae and S. cerevisiae reduced levels in coffee green beans (Purwoko et al 2022). However, there was no followed to detect compounds as the result of caffeine degradation.…”
Section: Introductionmentioning
confidence: 96%
“…Nonetheless, some microbes had the ability to degrade caffeine into its derivative, therefore, reducing the negative effects of caffeine. Lactic acid bacteria L. casei and L. mesenteroides and fungi S. cerevisiae and R. oryzae can reduce the caffeine content of robusta beans (Purwoko et al 2022).…”
Section: Introductionmentioning
confidence: 99%